New institutional economics in Viking studies. Visualising immaterial culture. (23rd December 2022) - Ögren, Anders; Hedenstierna-Jonson, Charlotte; Ljungkvist, John; Raffield, Ben; Price, Neil
Abstract: In this paper, we argue that closer engagement with the field of new institutional economics (NIE) has the potential to provide researchers with a new theoretical toolbox that can be used to study economic and social practices that are not readily traceable in material culture. NIE assumes that individual actions are based on bounded rationality and that the existence of rules (institutions) and their enforcement – the institutional framework – influences agents' actions by providing different incentives and probabilities for different choices. Within this theoretical framework, we identify a number of concepts, such as collective identity and mobile jurisdictions, that seem to fit what we know of Viking age economic systems. In applying these models to the available archaeological and textual data, we outline the ways in which further research could provide a new understanding of economic interaction within a rapidly evolving context of diaspora and change.